(untitled) (Tempo e Argumento, 2021)
This decade is being marked by a deep public perception of historical change and even as a beginning of a new epoch on a global scale. This paper argues that such a perception has political roots linked to the impact of political protests like June 2013 in Brazil and Occupy Wall Street in the Unitd States. Thus, we analyze the impact of such protests through the narratives and interpretations produced since their occurrence, focusing on books and newspaper articles in these coutries. We intend to contribute to the revision and complexification of the main hypotheses about contemporary historical time linked to the theories of “presentism” and “acceleration”, especially with regard to their conclusions about the current political situation as a setting for the collective experience of the future. Finally, we seek to reflect briefly on the possible responses of historical knowledge to such transformations. Keywords: demonstrations; social movement; temporality; presentism; june 2013.